Inorganic carbon is overlooked in global soil carbon research: A bibliometric analysis - Raza, Sajjad; Irshad, Annie; Margenot, Andrew; Zamanian, Kazem; Li, Nan; Ullah, Sami; Mehmood, Khalid; Ajmal Khan, Muhammad; Siddique, Nadeem; Zhou, Jianbin; Mooney, Sacha J.; Kurganova, Irina; et al. (Geoderma, 2024)
•This study quantified global soil C research trends and the proportional focus on SOC and SIC pools.•Soil inorganic C is an overlooked pool with only 4% share in global soil C research.•Approximately 40% of the soil C research was dedicated to climate change.•Soil C research is concentrated in few countries with 70% research contributed by 9 countries.•It is imperative to expand research focus on SIC to gain a comprehensive understanding of global C cycle. Soils are a major player in the global carbon (C) cycle and climate change by functioning as a sink or a source of atmospheric carbon dioxide (CO2). The largest terrestrial C reservoir in soils comprises two main pools: organic (SOC) and inorganic C (SIC), each having distinct fates and functions but with a large disparity in global research attention. This study quantified global soil C research trends and the proportional focus on SOC and SIC pools based on a bibliometric analysis and raise the importance of SIC pools fully underrepresented in research, applications, and modeling. Studies on soil C pools started in 1905 and has produced over 47,000 publications (>1.7 million citations). Although the global C stocks down to 2 m depth are nearly the same for SOC and SIC, the research has dominantly examined SOC (>96 % of publications and citations) with a minimal share on SIC (<4%). Approximately 40 % of the soil C research was related to climate change. Despite poor coverage and publications, the climate change-related research impact (citations per document) of SIC studies was higher than that of SOC. Mineral associated organic carbon, machine learning, soil health, and biochar were the recent top trend topics for SOC research (2020–2023), whereas digital soil mapping, soil properties, soil acidification, and calcite were recent top trend topics for SIC. SOC research was contributed by 151 countries compared to 88 for SIC. As assessed by publications, soil C research was mainly concentrated in a few countries, with only 9 countries accounting for 70 % of the research. China and the USA were the major producers (45 %), collaborators (37 %), and funders of soil C research. SIC is a long-lived soil C pool with a turnover rate (leaching and recrystallization) of more than 1000 years in natural ecosystems, but intensive agricultural practices have accelerated SIC losses, making SIC an important player in global C cycle and climate change. The lack of attention and investment towards SIC research could jeopardize the ongoing efforts to mitigate climate change impacts to meet the 1.5–2.0 °C targets under the Paris Climate Agreement of 2015. This bibliographic study calls to expand the research focus on SIC and including SIC fluxes in C budgets and models, without which the representation of the global C cycle is incomplete.